Characteristics of Garlic Crackers with Soy Flour Substitution (Glycine max. L) and Variations of Katuk Leaf Extract (Sauropus androgynus L) - Iklas Devi Ramadhan; Akhmad Mustofa; Nanik Suhartatik (Fakultas Sains dan Teknologi Unisri, 2026)
Garlic crackers are a snack made of starch-based ingredient with the addition of spices and leavening agents. In this study, garlic crackers were made with variations of tapioca flour, soy flour, and katuk leaf extract. Soy flour and katuk leaf extract were added to increase the nutritional value, especially to increase the protein and fiber content. This research aimed to formulate garlic crackers that will be preferred by the consumer and to determine the chemical, physical, and organoleptic properties of the product. The research used a factorial Completely Randomized Design (CRD) with two factors, namely the ratio of tapioca flour and soybean flour (90:10, 80:20, and 70:30) and variations of katuk leaf extract (5, 10, and 15%). The best formulation results that the most preferred by the panelist was cracker with 90% of tapioca flour, 10% soy flour, and 15% of katuk leaf extract. The garlic crackers have 3.75% of moisture, 2.22% of ash, 12.32% of fat, 5.82% protein, 75.90% carbohydrates, 1.93% crude fiber, development volume 86.57%, and organoleptic value of color 4.75 (like), taste 4.23 (like), aroma 4.25 (like), crispness texture 4.57 (like) and overall liking 4.50 (like). Garlic crackers substituted with soy flour and added with katuk leaf extract can increase the protein and fiber content.